Modelling and validating the multi-agent system behaviour for a washing machine production line - Leitão, Paulo (2012)
This paper describes the formal modelling and validation of the behaviour of a multi-agent system that integrates the production and quality control processes in a washing machine production line. The modelling, analysis and validation process uses the Petri nets formalism that provides a rigorous and formal language based on its powerful mathematical foundation, supporting the complete verification of the system correctness during the design phase and before to proceed to the deployment phase. The behaviour models of each agent belonging to the system architecture are edited, analysed and simulated in the PnDK framework.